(untitled) (Jóvenes en la Ciencia, 2018)
This study proposes the use of lamb waves, in the assessment of laminate carbon fibre-epoxy laminated materials with a PEEK-Graphene interleaved reinforcement, that was added in order to increase the interlaminar fracture toughness (IFT) of the material in Mode I and Mode II fracture. The main aim of this article is to provide insights of the inspection of CFRP laminates with added polymeric veils and their comparison with typical CFRP laminates using Lamb waves, stepping forward the research of inspection of reinforced composite with the ultrasonic technique. The results show the capability of lamb waves to propagate throughout interleaved composite materials and through damage zones inside them.